The Risk of Legitimizing Early Marriage: Legal Loopholes in Bangladesh’s Child Marriage Restraint Act 2017 - Riya, Subata Zannat; Halim, Abdul (Indonesian Journal of Community Development, 2025)
Introduction: The paper examines the threat of legitimizing child marriage by creating legal loopholes in the Child Marriage Restraint Act of 2017 in Bangladesh. The Act preserves the minimum legal age of marriage (18 years old in the case of girls, and 21 years old in the case of boys) as well as the exigency of punishment of child marriage, but rather controversially allows exceptions in unspecified special circumstances, with the consent of the parents and the court. Method: Based on secondary sources, policy analysis, and reports of NGOs, the present paper demonstrates that instead of preventing child marriage, the 2017 Act conforms to patriarchal values and increases gender inequality. Result: This paper stresses the view that the ambiguity has unintentionally opened among the forms of legitimization of underage marriage, especially with regard to girls who already encounter systemic disadvantages in health, education, and control. The absence of regulatory definitions, enforcement methods, and defense of the informants has resulted in a free-for-all situation in the rural areas. Conclusion: The paper suggests legislative revisions, increased monitoring, and community-based interventions so that legal loopholes can be sealed to prevent the early marriage of girls.